The summer olympics - Walsh, John Evangelist 1927- (Watts, 1979)
Presents a history of the summer Olympic Games, including brief sketches of 16 outstanding competitors, a tally of medals won by each country, and track and field records from 1896 through 1976.
Keywords: Geschichte; Athletes; Athletes -- Biography -- Juvenile literature; Olympics; Olympics -- History -- Juvenile literature; Biografie